Development and validation of an art-inspired multimodal interactive technology system for a multi-component intervention for older people: a pilot study - Camurri, Antonio; Seminerio, Emanuele; Morganti, Wanda; Canepa, Corrado; Ferrari, Nicola; Ghisio, Simone; Cera, Andrea; Coletta, Paolo; Barbagelata, Marina; Puleo, Gianluca; Nolasco, Ilaria; Costantini, Claudio; et al. (Frontiers in Computer Science, 2024)
The World Health Organization (WHO) acknowledges the presence of a significant body of research on the positive effects of the arts on health, considering a variety of factors including physical well-being, quality of life, and social and community impact. The model that underlies cultural welfare puts the performing arts, visual arts, and cultural heritage at the service of people personal and societal well-being. The potential connections between movements of the body and artistic content have been extensively studied over time, considering movement as a non-verbal language with a universal character. This pilot study presents the results of the validation of an innovative multimodal system, the DanzArTe-Emotional Wellbeing Technology, designed to support active and participative experience of older people that provides physical and cognitive activation through a full-body physical interaction with a traditional visual work of art of religious subject.DanzArTe supports a replicable treatment protocol for multidimensional frailty, administered through a low cost and scalable technological platform capable of generating real-time visual and auditory feedback (interactive sonification) from the automated analysis of individual as well as joint movement expressive qualities.The study involved 45 participants, 23 of whom participated in the DanzArTe program and 22 who wereincluded in the control group. The two groups were similar in terms of age (p=.465) and gender (p=.683).The results showed that the DanzArTe program had a positive impact on participants' self-perceived psychological health and well-being (Mean Psychological General Well-Being Index -ShortT1=19.6±4.3Vs. T2=20.8±4.9; p=.029). The same trend was not observed in the control group (p=.389).The findings suggest that such programs may have a significant impact particularly on the mental and social well-being of older adults and could be a valuable tool for promoting healthy aging and improving quality of life.